Directions for expanding the tax base and increasing the efficiency of information in the field of taxation and tax administration through the use of electronic documents (Eurasian Research Bulletin, 2025)
In order to further improve the tax system in our republic, reduce hidden circulation in the economy and implement the main directions of the concept of improving the fair tax policy of the Republic of Uzbekistan, the President of the Republic of Uzbekistan on July 10, 2019 "Additional measures to improve the tax administration" In order to further improve the activities of the Tax Service bodies, tasks such as automation of the Tax Administration process have been defined in the Decision No. PQ-4389. Also, it is more convenient for business entities that pay taxes on time and operate in compliance with legal requirements to ensure the implementation of the priority tasks set in the framework of the open dialogue of the President with entrepreneurs held on August 18, 2023. in order to create conditions and encourage them, by introducing digital technologies to the tax administration, expanding the tax base and some important reforms implemented in the tax system are studied, foreign experience, scientific and practical conclusions on its application in our country and proposals are developed.